Keys to interdisciplinarity between social work and anthropology: Reflections from the educational sphere - Ixone Fernández-de-Labastida, Ixone (Cuadernos de Trabajo Social, 2022)
The aim of this article is to examine certain keys to redirecting the social work training approach towards the interdisciplinary model, based on the intersection between social work and anthropology. Social work is practised in increasingly complex and culturally diverse contexts. This means that future social workers need to be trained in relational and dialogical thinking, as well as in holistic social intervention. Anthropological topics are commonly included in the social work degree curriculum in Spain and in practice there are multidisciplinary teams composed of social workers and anthropologists, especially in interventions involving cultural diversity and intercultural mediation. However, moving from a multidisciplinary to an interconnected training model requires a shift in approach. The interdisciplinary approach consists of jointly redefining the study/intervention object and aims. In short, there is an exceptional field for interdisciplinarity when anthropology is coupled with a critical and transformative model of social work.